PENGARUH TEKNIK SELF-MANAGEMENT TERHADAP PERENCANAAN KARIR - Istianingsih, Linda; Suarti, Ni Ketut Alit; Sulastri, Ni Made (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT Career planning is an important aspect of student development, especially at the senior high school level when students enter the exploration phase and begin determining their future direction. Observations conducted at SMAN 1 Praya Barat indicate that many Grade XI Social Science students do not yet have a clear picture of their future careers. This condition is reflected in low participation in self-development activities, limited reflection on personal potential, and weak time management and internal motivation. The purpose of this study was to determine the effect of self-management techniques on the career planning of Grade XI Social Science students at SMAN 1 Praya Barat in the 2024/2025 academic year. This study employed an experimental method using a one-group pretest–posttest design. The main data collection technique was a questionnaire, supported by observation, interviews, and documentation. Data were analyzed using a t-test. The results showed that the t-value was 13.312, which was greater than the t-table value of 2.015 at a 5% significance level, indicating that Ho was rejected and Ha was accepted. These findings demonstrate that self-management techniques have a significant effect on students’ career planning. This study highlights the importance of implementing self-management techniques in guidance and counseling services to improve students’ career readiness. ABSTRAK Perencanaan karir merupakan aspek penting dalam perkembangan peserta didik, terutama di jenjang pendidikan menengah atas, saat siswa memasuki fase eksplorasi dan penentuan arah masa depan. Hasil observasi di sekolah khususnya pada kelas XI IPS di SMAN 1 Praya Barat Tahun Pelajaran 2024/2025menunjukkan bahwa banyak siswa belum memiliki gambaran konkret mengenai karir masa depan. Hal ini tercermin dari rendahnya partisipasi dalam kegiatan pengembangan diri, kurangnya refleksi terhadap potensi pribadi, serta lemahnya pengelolaan waktu dan motivasi internal. Tujuan penelitian ini adalah untuk mengetahui pengaruh teknik self-management terhadap perencanaan karir pada siswa kelas XI IPS di SMAN 1 Praya Barat Tahun Pelajaran 2024/2025. Penelitian menggunakan metode eksperimen dengan desain one group pretest-posttest. Teknik pengumpulan data utama adalah angket, didukung observasi, wawancara, dan dokumentasi. Analisis data menggunakan uji-t. Hasil menunjukkan nilai t-hitung sebesar 13,312 lebih besar dari t-tabel 2,015 pada taraf signifikansi 5%, sehingga Ho ditolak dan Ha diterima. Artinya, terdapat pengaruh signifikan teknik self-management terhadap perencanaan karir siswa. Penelitian ini menegaskan pentingnya penerapan teknik self-management dalam layanan bimbingan untuk meningkatkan kesiapan karir peserta didik.